2018
DOI: 10.3390/fluids4010002
|View full text |Cite
|
Sign up to set email alerts
|

On the Generalized Kinetic Equation for Surface Gravity Waves, Blow-Up and Its Restraint

Abstract: This article is concerned with the non-linear interaction of homogeneous random ocean surface waves. Under this umbrella, numerous kinetic equations have been derived to study the evolution of the spectral action density, each employing slightly different assumptions. Using analytical and numerical tools, and providing exact formulas, we demonstrate that the recently derived generalized kinetic equation exhibits blow up in finite time for certain degenerate quartets of waves. This is discussed in light of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…e.g. [2,33], and the results of this paper could motivate analogous advances for those equations as well.…”
Section: Applicationsmentioning
confidence: 61%
“…e.g. [2,33], and the results of this paper could motivate analogous advances for those equations as well.…”
Section: Applicationsmentioning
confidence: 61%
“…2.19] generalized this to include frequency correction terms. The same generalized equation was recently studied by Andrade et al [6], and found to exhibit finite-time blow-up for some degenerate quartets. When performing Monte-Carlo simulations, Annenkov & Shrira [7,Sec.…”
Section: The Role Of Near-resonant Interactionsmentioning
confidence: 59%
“…A number of generalizations of the kinetic equation (27) [6], and found to exhibit finite-time blow-up for some degenerate quartets. When performing Monte-Carlo simulations, Annenkov & Shrira [7,Sec.…”
Section: The Role Of Near-resonant Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…All these limitations of our GKE algorithm would practically inhibit its large-scale, realistic applications. Andrade, Stuhlmeier & Stiassnie (2019) reported that when applied to degenerate quartets, the GKE may exhibit blow-up under certain conditions, further implying a possible inherent deficiency of the GKE. Such strange behaviour, however, is not observed in our simulations for wave spectra with multiple wave modes.…”
Section: Applicability For 2-d Simulationsmentioning
confidence: 99%